Primary small cell carcinoma of the thyroid: a case report - Prado, Maria Clara Martins; Staino, Isabella Rocha França Longo; Silva, Hannah Damasceno Barreto da; Castro, Alexandre Fonseca de; França, Lysio; Barros, Paula Ferreira (Brazilian Journal of Oncology, 2019)
The diagnosis of cervical mass is a challenge due to the wide variety of benign and malignant etiologies. Extrapulmonary small cell carcinomas (EPSCC) are rare entities, and those tumours arising as a primary cervical, especially in the thyroid gland, are exceedingly rare. As others small cell neuroendocrine carcinomas, the disease has an aggressive behavior. This case report is about a 40-years-old female patient admitted to the Hospital Felício Rocho, with airway compression caused by a cervical mass originated in the thyroid gland. The data were extracted from the medical records and information provided by the attendants. We describe here the multidisciplinary approach used to treat the patient as well as her outcome. We also review the clinical and molecular aspects of this rare entity.
Keywords: Carcinoma; Neuroendocrine tumors; Thyroid gland; Molecular biology; Diagnosis; Differential.